2008
DOI: 10.1007/s11274-008-9883-3
|View full text |Cite
|
Sign up to set email alerts
|

Vertical distribution of bacterial community structure in the sediments of two eutrophic lakes revealed by denaturing gradient gel electrophoresis (DGGE) and multivariate analysis techniques

Abstract: Vertical distribution of bacterial community structure was investigated in the sediments of two eutrophic lakes of China, Lake Taihu and Lake Xuanwu. Profiles of bacterial communities were generated using a molecular fingerprinting technique, denaturing gradient gel electrophoresis (DGGE) followed by DNA sequence analysis, and the results were interpreted with multivariate statistical analysis. To assess changes in the genetic diversity of bacterial communities with changing depth, DGGE banding patterns were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
46
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 47 publications
7
46
0
Order By: Relevance
“…This method provides the possibility to identify the community members by reamplifying and sequencing of the excised bands. Previously, DGGE technique was successfully applied to reveal the alterations of bacterial or total microbial communities in freshwater and seawater habitats infl uenced by different environmental factors [10,11,12,13,14]. According to the UPGMA dendrogram based on the DGGE patterns, signifi cant seasonal changes with less spatial differences were found among the total planktonic bacterial communities of Lake Hévíz (Fig.…”
Section: Microbial Community Structuresmentioning
confidence: 99%
“…This method provides the possibility to identify the community members by reamplifying and sequencing of the excised bands. Previously, DGGE technique was successfully applied to reveal the alterations of bacterial or total microbial communities in freshwater and seawater habitats infl uenced by different environmental factors [10,11,12,13,14]. According to the UPGMA dendrogram based on the DGGE patterns, signifi cant seasonal changes with less spatial differences were found among the total planktonic bacterial communities of Lake Hévíz (Fig.…”
Section: Microbial Community Structuresmentioning
confidence: 99%
“…Notably, TP, Cu and Cd were important factors affecting bacterial community in surface sediment of Poyang Lake. TP played an important role in driving the changes in water column and sediment bacterial communities of freshwater Lake [4,15]. And it has been reported that phosphorus concentration is associated with the phosphate-dissolving and phosphate-decomposing bacteria in the sediments [19].…”
Section: Controlling Environmental Factors On Microbial Communitymentioning
confidence: 99%
“…Huang et al [3] found that distribution of bacteria was affected by the combined effects of various dissolved inorganic matter in sediments of Pearl River, China. Total phosphorus and pH were characterized as significant environmental factors correlated with bacterial communities in the sediment of eutrophic lake [4]. Furthermore, it was reported that heavy metals have accumulative toxic effects on cells and they tend to be bound on sediments and removed from the water [5].…”
mentioning
confidence: 99%
“…4 B,C). pH may not only reflect changes in other environmental factors (KoskiVähälä et al, 2001), which can have both inhibitory and stimulative effects on bacterial communities (Zeng et al, 2009), but may also influence bacterial communities through direct biological mechanisms (Yannarell and Triplett, 2005).…”
Section: Environmental Factors Regulating the Bacterial Community Commentioning
confidence: 99%